Diversity of Soil Arthropods in the Ranu Pani Restoration Area: An Indicator of Mountain Ecosystem Recovery - Ardillah, Jr Sulthan (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to identify the diversity of soil arthropods in the restoration area of Ranu Pani, Lumajang, determine the ecological roles of each arthropod group, and analyze the diversity index as an indicator of ecosystem condition and restoration progress in the study area. Methodology: Descriptive research design with block plot sampling, pitfall trap method using plastic cup traps, digital thermometer, lux meter, binocular microscope, alcohol preservation solution, field observation, ecological identification keys, abiotic factor measurement, Shannon-Wiener diversity index analysis, Important Value Index calculation, density and frequency analysis, supported by literature review. Main Findings: A total of 916 soil arthropod specimens belonging to 9 orders and 13 families were collected. Diversity index was higher in the first-year location (H’ = 2.523) than the second-year location (H’ = 1.899). Dominant families were Gryllidae and Talitridae. Ecological roles consisted of predators, herbivores, scavengers, and parasitoids, with herbivores and scavengers showing the highest proportions across restoration sites. Novelty/Originality of this study: This study provides updated ecological baseline data on soil arthropod diversity in Ranu Pani restoration areas by integrating diversity, community structure, ecological roles, and abiotic factors. It advances restoration ecology knowledge by demonstrating the use of soil arthropods as bioindicators for assessing ecosystem recovery and restoration effectiveness in highland conservation landscapes.